Ageing and globalisation - Hyde, Martin, 1960-; Higgs, Paul (Ageing in a global context., 2016)
Population ageing and globalisation represent two of the most radical social transformations that have occurred. This book provides, for the first time, an accessible overview of how they interact. Ageing has been conventionally framed within the boundaries of nation states, yet demographic changes, transmigration, financial globalization and the global media have rendered this perspective problematic. This much-needed book is the first to apply theories of globalisation to gerontology, including Appadurai's theory, allowing readers to understand the implications of growing older in a global age. This comprehensive introduction to globalisation for gerontologists is part of the Ageing in a Global Context series, published in association with the British Society of Gerontology. It will be of particular interest to advanced undergraduate and postgraduate students and academics in this area.